2007
DOI: 10.1021/jp0717600
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Atom Tunneling in 2-Chlorobenzoic Acid Studied by Low-Temperature Matrix-Isolation Infrared Spectroscopy

Abstract: Intramolecular hydrogen atom tunneling in 2-chlorobenzoic acid has been investigated by low-temperature matrix-isolation infrared spectroscopy with the aid of density functional theory calculation. Infrared spectra of two relatively stable syn isomers, SC and ST, were observed in argon and xenon matrixes. When the matrix samples were annealed after deposition, the isomerization from ST to SC occurred around the benzene-carboxyl bond. Two less stable anti isomers, AT, which has an OH...Cl intramolecular hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 23 publications
5
47
0
2
Order By: Relevance
“…Hence, it seems possible that these two processes, once occurring simultaneously, lead to a stationary population ratio. The most plausible rationalization for the mechanism of back isomerization of ALA conformer VI to conformer I, in the dark at 14 K, is the occurrence of a tunneling decay, as reported previously for other matrixisolated molecules containing the carboxylic fragment, such as formic, 35 acetic, 29,36 propionic, 37 2-chloropropionic, 38 benzoic 39,40 acids, glycine, 31 and other systems, for example, hydroxycarbene. 41 Actually, if thermal isomerization is involved, form VI could be transformed into form IIa (via forms VIIIa or VIIIb) instead of isomerization into form I, since this process has a much lower energy barrier (i.e., 8-10 kJ mol −1 versus 30 kJ mol −1 , respectively; as compared graphically in Figs.…”
Section: The Decay Mechanism Of L-alanine High-energy Conformer VIsupporting
confidence: 60%
“…Hence, it seems possible that these two processes, once occurring simultaneously, lead to a stationary population ratio. The most plausible rationalization for the mechanism of back isomerization of ALA conformer VI to conformer I, in the dark at 14 K, is the occurrence of a tunneling decay, as reported previously for other matrixisolated molecules containing the carboxylic fragment, such as formic, 35 acetic, 29,36 propionic, 37 2-chloropropionic, 38 benzoic 39,40 acids, glycine, 31 and other systems, for example, hydroxycarbene. 41 Actually, if thermal isomerization is involved, form VI could be transformed into form IIa (via forms VIIIa or VIIIb) instead of isomerization into form I, since this process has a much lower energy barrier (i.e., 8-10 kJ mol −1 versus 30 kJ mol −1 , respectively; as compared graphically in Figs.…”
Section: The Decay Mechanism Of L-alanine High-energy Conformer VIsupporting
confidence: 60%
“…Indeed, the placement of the nearest nitro O relative to the flavin N5 is most compatible with anti transfer of hydride as opposed to the more favorable and common syn transfer (Fig. 6B, (Nishino and Nakata, 2007)). However the geometry allows that the required proton could be acquired from an active site solvent molecule or a proton temporarily resident near N1 via favorable syn proton transfer.…”
Section: Discussionmentioning
confidence: 99%
“…For several molecules containing a carboxylic group, and where high-energy conformers could be successfully produced in situ in cryogenic matrices by near-IR pumping of a lower energy precursor conformer, it has been observed that back-isomerization can take place spontaneously in the dark, by tunneling. 57,[66][67][68][69][70][71] In the present study, we have also investigated this possibility for TAA.…”
Section: Spontaneous Decay (By Tunneling) Of the High-energy Conformementioning
confidence: 99%